MODIFIKASI ALGORITMA VIGENERE CIPHER UNTUK PENGAMANAN PESAN RAHASIA - Jesmon Simangunsong; zekson Arizona Matondang (UPPM, 2018)
The confidentiality of messages or data owned by someone is important in sending messages sothat the message can only be given by certain people who can access the information. Cryptography isthe study of how to safeguard data or messages with the aim of preventing others from wanting to knowtheir contents, by using certain codes and rules and other methods so that only authorized people canfind out the true contents of the message. In the Vigenere Cipher algorithm the message security usesonly a single key and the alphabet as an encoding key to replace or substitution the character of themessage which makes the strength in the message transmission limited only to the use of the alphabet.In this research, the Vegenere Cipher algorithm was modified with 3 keys used and the vegenere ciphertable modified by adding numbers and 10 symbols so that the characters of the table are 46 charactersfrom the previous 26 characters. The results of this algorithm are able to encrypt secret messages anddecrypt them back into their original messages.